Effect of adding Inulin on some physicochemical and sensory properties of yoghurt (Latakia University Journal -Biological Sciences Series, 2022)
The research aims to study the effect of using Inulin with different concentrations (0.5-1-1.5-2) % on the temperature (7±1) °C for 15 days in the chemical composition for yoghurt. The results showed that the treatment with 2% of Inulin concentration was significantly superior to each of the full-fat control, the low-fat control and the rest of the treatments especially when estimating ash which amounted to 0.65%, moisture amounted to 88.63% and acidity which amounted to 0.91%, the protein percentage was close to all treatments. According to the fat, a significant decrease was observed in all the processed treatments of sorted milk. It was particularly noted that 2% of Inulin added to the low-fat yoghurt improved the sensory properties which obtained the highest sensory evaluation values. The results showed had a slight decrease in moisture and fat values for all treatments during the storage period. The protein percentage was close to all treatments. The results showed the percentage of Inulin 2% which achieved the highest values in the percentage of ash and acidity than the rest of the treatments. The results of the sensory evaluation proved that increasing the percentage of added Inulin, improved the sensory properties of the stored yoghurt and the best values were when the percentage of adding inulin 2%.